Effects of temperature and water content on bacterial community composition in a tropical and an antarctic soil, based on microcosm studies in the laboratory / Yasoga Supramaniam - Yasoga, Supramaniam (2017)
Environmental factors such as temperature and water content play crucial roles in shaping the dynamics of soil bacterial community which in turn influences the ecosystem functioning. Alteration in any of these factors might alter the structure, composition and abundance of soil bacterial community. In this study, effects of temperature and water content on bacterial community in a tropical soil and an Antarctica soil were elucidated using laboratory-based microcosm studies. Tropical soil microcosms were incubated at 25°C, 30°C, 35°C, and subjected to low or high water treatments (2 ml or 5 ml respectively). The microcosms were analysed at Weeks 1, 2 and 4. Antarctic soil microcosms were incubated at 5°C, 10°C, 15°C with no variation in water treatment, and analysed at Weeks 4, 8 and 12. Bacterial richness, abundance and composition were analysed by terminal restriction fragment length polymorphism (T-RFLP) and high-throughput next generation sequencing. Functional genes (nifH, amo-A, nirS, nirK, nosZ and Chitinase GA) abundance was determined by quantitative polymerase chain reaction (Q-PCR). Abiotic parameters (pH, electrical conductivity, moisture, nitrate, nitrite and phosphate) in the microcosms were also measured.Results indicated that both structure and composition of tropical soil bacterial community differed significantly across the treatments. The relative abundance of Firmicutes, the dominant phylum, correlates positively with temperature and water content, and the highest compositional shifts were observed in the Week 2 microcosms. On the other hand, only subtle difference in Antarctic soil bacterial community structures was detected across temperature. Nevertheless, bacterial assemblages were strongly structured by period of incubation. Antarctic soil samples were dominated by Proteobacteria which responded positively to temperature upshift. Distance-based linear model (DISTLM) analysis showed that pH, electrical conductivity, nitrate, nitrite and moisture content were the most significant parameters that correlated with the tropical soil bacterial community. In contrast, soil nitrate content was the sole parameters found to correlate with the Antarctic soil bacterial community. Significant correlations were found between tropical soil bacterial communities and the nitrogen fixation gene (nifH) and denitrification gene (nosZ) whereby an increase of nifH gene copies was observed with increase in temperature. In the Antarctic soil microcosms, the nosZ and GA genes showed the highest correlation to the bacterial community. Collectively, the above findings indicate that changes in temperature and water content induced shifts in soil bacterial community composition, abiotic parameters and functional gene abundance.